The work of Živojin Perić on the codification of the Civil Code of interwar Yugoslavia - Mirković Zoran S. (Anali Pravnog Fakulteta u Beogradu)
Živojin Perić's work on codifying the civil code was analyzed through four questions. 1) Participation in the work of the body for drafting the Civil Code and its work on the text of the Code. 2) Perić's opinion on the codification method that was applied. 3) Perić's opinion on the legal terminology in the 1934 Draft Civil Code for the Kingdom of Yugoslavia. 4) Perić wrote the explanation (motives) 1-319. paragraph of the Draft Civil Code, which was officially published by the Ministry of Justice in 1939.